The development of usability scales for flight management systems (volumes one and two) - Lane, Karen P. (Cranfield University, 2002)
Usability is a multidimensional concept, and although a number of techniques have been developed for assessing usability, none have been developed specifically for the civil flight deck or its components. The requirement for Human Factors tools to support civil flight deck certification have been well documented (e.g. FAA, 1996). This thesis reports on a research programme that resulted in the development of a series of scales to assess the usability of Flight Management System (FMS) Control and Display Units (CDUs). Since the goal of this research was to produce scales that could be used by certification authorities and FMS manufacturers, demonstrating that the scales had appropriate psychometric properties was critical. A rigorous and systematic approach to the construction of the usability scales was therefore adopted. The research was conducted in three studies. The first study involved the development of a 49-item questionnaire that was distributed to airline pilots. A series of analyses on the data collected demonstrated that a reliable and valid usability factor structure was produced. The second study focused on the production of usability scales and examined the impact of flight phase on usability ratings. Analyses demonstrated that the factor structure produced in the first study was reliable, and was valid for data collected for the cruise and descent and approach phases of flight. A series of internally consistent usability scales was therefore produced which demonstrated evidence of discriminant, face, content, and construct validity. The third study involved a content analysis on a large volume of participant comments derived during studies one and two, and examined the usability problems associated with current FMSs and suggested improvements for future FMSs. The content analysis produced evidence of construct validity for the usability scales developed, and permitted recommendations for FMS designers and certification authorities to be made.